PENGARUH INSENTIF FINANSIAL DAN KARAKTERISTIK INDIVIDUAL TERHADAP KINERJA PEGAWAI PADA DINAS PERIZINAN KABUPATEN TAPANULI TENGAH - Joshua Hans Moan Lumban Tobing; Mansur Tanjung; Yusi Tri Utari Panggabean (CV. ALIM'SPUBLISHING, 2023)
One of the goals of providing financial incentives is to encourage employees to have high performance. Besides that, individual characteristics make a difference when they are given assignments. But in reality the performance shown by employees is less than optimal. The purpose of this study was to find out whether financial incentives and individual characteristics jointly influence the performance of employees at the Central Tapanuli District Licensing Service. The hypothesis that the author proposes is that financial incentives and individual characteristics jointly influence the performance of employees at the Licensing Service of Tapanuli Tenga Regency. The population is 34 people and used as a sample. The results of the study found that financial incentives and individual characteristics simultaneously had a positive effect on employee performance at the Central Tapanuli District Licensing Service, where Fcount (44.747) > Ftable (3.13) Partially the financial incentive variable had the most dominant effect on employee performance, where the t-value count 4.056 > ttable value 2.004 Partially individual characteristic variables have a positive and significant effect on employee performance, where the t-count value is 2.823 > ttable value 2.004 (2.823 > 2.004) 55.4% employee performance can be influenced by financial incentives and individual characteristics. It is recommended that agencies need to pay attention to employees, especially THL, by providing financial incentives, not just employees with civil servant status, because the service wheels for the community serve more THL